GAYA TULISAN KEPEMIMPINAN DAHLAN ISKAN DALAM KOLOM MANUFACTURING HOPE HARIAN SUMUT POS - Endang Wahyuningsi (STKIP Pesisir Selatan, 2018)
This study aims to describe Dahlan Iskan style of writing in Column Manufacturing Hope Sumut Pos. This type of research is qualitative research with descriptive method. The object of this research is column in Sumut Pos written by Dahlan Iskanat the date of 6,13, and 20 may 2013. Data collection techniques are documentation.the results of this study is Dahlan Iskan Style of writing in column manufacturing Hope Sumut Pos (1) based on how the author expresses his attitude is people who know everything (using my pronoun) and (2) based on the variety of languages is less formal language and literary variety. Based on writing style then it can be seen that Dahlan Iskan is an all-knowing person, a person who reflects on the past,and Dahlan Iskan is a person who always uses good and proper Indonesian in accordance with the context and situation so that Dahlan Iskan is someone whohas a relaxed attitude and not rigid, and Dahlan Iskan including people who oftenuse the style of language in writing, for example using personification, irony,hyperbole, and metaphor.Key word: write style, leader, column, Sumut Pos, Dahlan Iskan